228Ra, 226Ra and 210Pb in sediment and water of the São Francisco River in Petrolina-PE/Brazil. (1st January 2013) - Silva, C.M.; Tabosa, J.N.; Costa Júnior, C.E.O.; Silva Filho, C.A.; Souza Neto, J.A.
The purpose of this of this research is to determine 228 Ra, 226 Ra and 210 Pb concentrations in the water and sediment of the São Francisco River, nearby from farms producing fruits in Petrolina City. Concentrations of 228 Ra, 210 Pb and 226 Ra in the water samples varied from < 19.0 (detection limit) to 22.0 mBq.l –1 ; < 4.0 (detection limit) to 13.0 mBq.l –1 ; and 12.0 to 42.0 mBq.l –1, respectively. For sediments samples, in this order, the concentrations ranged from < 7.0 (detection limit) to 35.0 Bq.kg –1 ; < 3.5 (detection limit) to 15.0 Bq.kg –1 ; and 12.0 to 92 Bq.kg –1 . These results indicate that there are spots in São Francisco Rive, Petrolina, which have high concentrations of 228 Ra, 226 Ra and 210 Pb in sediments.